Use of voltammetry for in vitro equilibrium and transport studies of ionisable drugs - Matej Velicky; Andrew Norman John Rodgers; Robert Angus William Dryfe; Kin Y Tam (International Association of Physical Chemists (IAPC), 2014)
In this review, we will briefly outline the voltammetric investigations of the transfer of ionisable drugs at the interface between two immiscible electrolyte solutions. The voltammetric techniques enable the determination of some key in vitro properties of ionisable drugs, including partition coefficient, diffusion coefficient and membrane permeability. Some successful applications will be highlighted, together with the background methodologies.